Lessons from GPS-tagged Eurasian Curlews: synthesising movement ecology to inform conservation - Frédéric Jiguet; Aurélien Besnard; Pierrick Bocher; Andrea Kölzsch; Aleksi Lehikoinen; Markus Piha; Petr Procházka; Marie Donnez; Tuomas Seimola; Jimmy Allain; Lise Bartholus; Carole Doucerain; et al. (Biological Conservation, 2026)

Quantifying quaternary climate variability in the Southern Caucasus using land snail shell isotope transfer functions and climatic niche modeling - Christiane Richter; Michael Schneider; Daniel Wolf; Frank Walther; Bernhard Hausdorf; Hayk Hovakimyan; Lilit Sahakyan; Markus Fuchs; Dominik Faust (Quaternary Science Reviews, 2026)

Multi-method luminescence dating of late Cenozoic northern Upper Rhine Graben fluvial sediments - Anna-Lena Geis; Mariana Sontag-González; Thomas Kolb; Mayank Jain; Markus Fuchs (Quaternary Geochronology, 2025)

The ad-libitum taste test as measure of momentary alcohol use in the laboratory: an investigation of construct validity and confounding factors - Sebastian Trautmann; Anja Kräplin; Markus Muehlhan; Fée Ona Fuchs; Beate Loesch; Charlotte Wittgens (Psychopharmacology, 2024)
Rationale The ad-libitum taste test is a widely used covert measure of motivation to consume alcohol in the laboratory. However, studies on its construct validity and potential confounding factors are scarce. Objectives This study aimed to evaluate the construct validity of the ad-libitum taste test by examining the association of ad-libitum alcohol consumption with typical alcohol use and craving, and investigating potential moderation by trait anxiety, depressiveness, current mood, and drinking motives. Methods A sample of 264 young male individuals were offered two 0.33 l glasses of beer. Participants were instructed to rate the characteristics of each drink, while the percentage of beverages containing alcohol consumed was assessed. Associations of ad-libitum consumption with typical alcohol use and craving were assessed using non-parametric and piecewise regressions. Moreover, moderator analysis with trait anxiety, depressiveness, current mood, and drinking motives was carried out. Results Ad-libitum alcohol consumption was associated with typical alcohol use and alcohol craving. However, these associations decreased at high consumption levels. Associations between ad-libitum consumption, typical alcohol use, and craving were stable across several conditions, except that the association between ad-libitum consumption and craving increased with higher social, conformity, and coping drinking motives. Conclusions The ad-libitum taste test appears to be a valid measure of the motivation to drink alcohol in laboratory studies in young male adults, although this validity might be compromised at high levels of ad-libitum consumption. Consideration of these factors can contribute to further refining the ad-libitum taste test as a valuable tool for assessing motivation to consume alcohol in laboratory studies.

Archaeopedological reconstruction of Middle Bronze Age subsistence farming in SW-Germany from sedimentary archives in the Western Allgäu - Sascha Scherer; Benjamin Höpfer; Katleen Deckers; Markus Fuchs; Ellen Kandeler; Eva Lehndorff; Johanna Lomax; Sven Marhan; Christian Poll; Wroth Kristen; Thomas Knopf; Thomas Scholten; et al. (Geoderma Regional, 2023)

Knockout mouse models as a resource for the study of rare diseases - Patricia da Silva-Buttkus; Nadine Spielmann; Tanja Klein-Rodewald; Christine Schütt; Antonio Aguilar-Pimentel; Oana V. Amarie; Lore Becker; Julia Calzada-Wack; Lillian Garrett; Raffaele Gerlini; Markus Kraiger; Stefanie Leuchtenberger; et al. (Mammalian Genome, 2023)
Rare diseases (RDs) are a challenge for medicine due to their heterogeneous clinical manifestations and low prevalence. There is a lack of specific treatments and only a few hundred of the approximately 7,000 RDs have an approved regime. Rapid technological development in genome sequencing enables the mass identification of potential candidates that in their mutated form could trigger diseases but are often not confirmed to be causal. Knockout (KO) mouse models are essential to understand the causality of genes by allowing highly standardized research into the pathogenesis of diseases. The German Mouse Clinic (GMC) is one of the pioneers in mouse research and successfully uses (preclinical) data obtained from single-gene KO mutants for research into monogenic RDs. As part of the International Mouse Phenotyping Consortium (IMPC) and INFRAFRONTIER, the pan-European consortium for modeling human diseases, the GMC expands these preclinical data toward global collaborative approaches with researchers, clinicians, and patient groups. Here, we highlight proprietary genes that when deleted mimic clinical phenotypes associated with known RD targets ( Nacc1, Bach2, Klotho alpha ). We focus on recognized RD genes with no pre-existing KO mouse models ( Kansl1l, Acsf3, Pcdhgb2, Rabgap1, Cox7a2 ) which highlight novel phenotypes capable of optimizing clinical diagnosis. In addition, we present genes with intriguing phenotypic data ( Zdhhc5, Wsb2 ) that are not presently associated with known human RDs. This report provides comprehensive evidence for genes that when deleted cause differences in the KO mouse across multiple organs, providing a huge translational potential for further understanding monogenic RDs and their clinical spectrum. Genetic KO studies in mice are valuable to further explore the underlying physiological mechanisms and their overall therapeutic potential.

Anthropogenic impact on erosion, pedogenesis and fluvial processes in the central European landscapes of the eastern Harz mountains forelands (Germany) - Stefan Dreibrodt; Carolin C.M. Langan; Markus Fuchs; Hans-Rudolf Bork (Quaternary Science Reviews, 2023)

Construction and use of rock-cut cisterns: a chronological OSL approach in the arid Negev Highlands, Israel - Andrea Junge; Zachary C. Dunseth; Ruth Shahack-Gross; Israel Finkelstein; Markus Fuchs (Archaeological and Anthropological Sciences, 2021)
The Negev Highlands (Israel) are characterized by a rich settlement history over the last millennia. To sustain life in this arid environment, measures to collect and store water were introduced. Two types of installations to collect and store runoff water were built in the region: open reservoirs, and more elaborate subterranean rock-cut cisterns. This article focuses on the latter. Based on a few inscriptions found in rock-cut cisterns, it is assumed that the majority were constructed in the Hellenistic (Nabatean) to Byzantine period. To evaluate this age assessment, this study was carried out at the Borot Hazaz cisterns system, using optically stimulated luminescence (OSL) dating together with micromorphological analyses. Both were applied to sediments that were relocated during the cistern’s construction and usage and after the maintenance activities ended. Despite unfavourable conditions for resetting the OSL signal, including fluvial transport over short distances and sediment deposition by humans in large quantities, it was possible to reconstruct the life cycle of the cistern system. The present study places the construction of the system during the late Roman to Byzantine period, with utilization and long-term maintenance during the following centuries. Maintenance ceased at the Borot Hazaz cistern system gradually over the course of the last 500 years.

Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites - Jacob A. Nelson; Oscar Pérez‐Priego; Sha Zhou; Rafael Poyatos; Yao Zhang; Peter D. Blanken; Teresa E. Gimeno; Georg Wohlfahrt; Ankur R. Desai; Beniamino Gioli; Jean‐Marc Limousin; Damien Bonal; et al. (Global Change Biology, 2020)
We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants’ water use for global water and carbon cycling in a changing climate.

New insights into Southern Caucasian glacial–interglacial climate conditions inferred from Quaternary gastropod fauna - Christiane Richter; Daniel Wolf; Frank Walther; Stefan Meng; Lilit Sahakyan; Hayk Hovakimyan; Tilmann Wolpert; Markus Fuchs; Dominik Faust (Journal of Quaternary Science, 2020)
In the present study, we performed gastropod analyses on loess–palaeosol sequences from northeast Armenia (Southern Caucasia) covering at least three glacial–interglacial cycles. The elaborated ecostratigraphy shows significant patterns of species composition related to the succession of pedocomplexes and loess, respectively. Pedocomplexes included species that can be associated with high‐grass to forest‐steppe biomes, indicating increased humidity for these sections compared to the loess layers. In contrast, loess layers that relate to glacial periods are associated with gastropod species of semidesert environments with shrub‐ and shortgrass‐steppes, indicating semiarid to arid conditions. Furthermore, the loess deposits do not show any evidence for cold‐adapted gastropod species. Therefore, we suggest that average July temperatures in the study area were above 10 °C, even during periods of loess deposition. Consequently, we propose that the limiting factor for tree growth during glacial periods was aridity, rather than temperature. In addition, we observe environmental differences between the various glacial times, with our results indicating a trend towards steadily increasing aridity in Southern Caucasia across the Middle to Late Pleistocene.

Climate Change driven evolution of hazards to Europe’s transport infrastructure throughout the twenty-first century - Christoph Matulla; Brigitta Hollósi; Konrad Andre; Julia Gringinger; Barbara Chimani; Joachim Namyslo; Tobias Fuchs; Markus Auerbach; Carina Herrmann; Brigitte Sladek; Heimo Berghold; Roland Gschier; et al. (Theoretical and Applied Climatology, 2018)

Paleolimnological features of a mega-lake phase in the Makgadikgadi Basin (Kalahari, Botswana) during Marine Isotope Stage 5 inferred from diatoms - Mareike Schmidt; Markus Fuchs; Andrew C. G. Henderson; Annette Kossler; Melanie J. Leng; Anson W. Mackay; Elisha Shemang; Frank Riedel (Journal of Paleolimnology, 2017)

Enhanced aphid abundance in spring desynchronizes predator–prey and plant–microorganism interactions - Benjamin Fuchs; Tatjana Breuer; Simone Findling; Markus Krischke; Martin J. Mueller; Andrea Holzschuh; Jochen Krauss (Oecologia, 2017)

Peramine and Lolitrem B from Endophyte-Grass Associations Cascade Up the Food Chain - Benjamin Fuchs; Markus Krischke; Martin J. Mueller; Jochen Krauss (Journal of Chemical Ecology, 2013)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Pflanzen neu entdecken: Rheinauer Thesen zu Rechten von Pflanzen - Florianne Koechlin; Daniel Ammann; Eva Gelinsky; Benny Haerlin; Martin Ott; Beat Sitter-Liver; Werner Stumpf; Edgar Wagner; Amadeus Zschunke; Günter Altner; Nikolai Fuchs; A. Heistinger; et al. (Journal of Consumer Protection and Food Safety, 2009)

Optimization of nonviral transfection: variables influencing liposome-mediated gene transfer in proliferating vs. quiescent cells in culture and in vivo using a porcine restenosis model - Jaroslav Pelisek; Markus Engelmann; Adam Golda; Alexandra Fuchs; Sorin Armeanu; Masumi Shimizu; Choukri Mekkaoui; Pierre Rolland; Sigrid Nikol (Journal of Molecular Medicine, 2002)

Mutations of the gene encoding the transmembrane transporter protein ABC-C6 cause pseudoxanthoma elasticum - Berthold Struk; Li Cai; Stéphanie Zäch; Wan Ji; Joon Chung; Amanda Lumsden; Markus Stumm; Marcel Huber; Lori Schaen; Chung-Ah Kim; Lowell A. Goldsmith; Denis Viljoen; et al. (Journal of Molecular Medicine, 2000)

A 500-kb region on chromosome 16p13.1 contains the pseudoxanthoma elasticum locus: high-resolution mapping and genomic structure - Li Cai; Berthold Struk; Mark D. Adams; Wan Ji; Thomas Haaf; Hyung-Lyun Kang; So Hee Dho; Xuequn Xu; Franziska Ringpfeil; Julie Nancarrow; Stéphanie Zäch; Lori Schaen; et al. (Journal of Molecular Medicine, 2000)